Positive electrode material, lithium ion battery and preparation method

By using a fluorine-doped lithium cobalt oxygen material coating layer on the nickel-cobalt-manganese ternary material, the valence state of the Co element and the distribution of fluorine ions are controlled, which solves the problems of short cycle life and unstable layered structure of the material under high voltage. , achieving better cycle capability and capacity performance.

CN119361656APending Publication Date: 2025-01-24XTC NEW ENERGY MATERIALS(XIAMEN) LTD
View PDF 0 Cites 5 Cited by

Patent Information

Application Number
CN202411616404.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-13
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

The existing nickel, cobalt, manganese ternary materials have short cycle life at high voltages, which are prone to side reactions and unstable layered structures, resulting in capacity attenuation and increased impedance.

Method used

Fluorine-doped lithium cobalt oxide material is used as the coating layer. By adding excess lithium and fluorine elements to the cobalt coating layer, the valence state of the Co element is controlled, and the concentration gradient distribution of fluorine ions is used to improve the material's performance at high voltages. stability under.

Benefits of technology

It significantly improves the circulation capacity, capacity, and low impedance performance of the material under high voltage, prolonged the cycle life, and reduced the instability of the side reaction and layered structure.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119361656A_ABST
    Figure CN119361656A_ABST
Patent Text Reader

Abstract

The invention provides a positive electrode material, a lithium ion battery and a preparation method, and relates to the technical field of battery materials. The positive electrode material comprises an inner core and a coating layer, the inner core is a ternary material matrix, the coating layer is a fluorine-doped lithium cobalt oxide material, the lithium cobalt oxide material contains Co < 2 + > and Co < 3 + >, and in the coating layer, the fluorine element and the Co < 2 + > are both distributed progressively from the surface to the center. The positive electrode material effectively improves the capacity fading problem under high voltage, and shows excellent circulation capability, high capacity and low impedance under high voltage.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium batteries, and in particular to a positive electrode material, a lithium ion battery and a preparation method thereof. Background Art

[0002] Lithium-ion batteries have been widely used in 3C digital, vehicle power, power station energy storage and other fields. The positive electrode material is an important component of lithium-ion batteries, and the nickel-cobalt-manganese ternary material is one of the most popular positive electrode materials.

[0003] Ternary materials can be divided into polycrystalline and single crystal types according to their morphology. Compared with ternary polycrystalline materials, ternary single crystal materials have a smaller specific surface area, fewer active sites in contact with the electrolyte, and fewer side reactions; and ternary single crystal materials have high mechanical strength. Therefore, the thermal stability and cycle stability of ternary single crystal materials are more advantageous.

[0004] However, with the rapid development of electric vehicles and large-scale energy storage, the energy density of rechargeable lithium-ion batteries is facing huge challenges at this stage. Nickel-cobalt-manganese ternary materials are also gradually developing in the direction of high voltage and high nickel. However, with the increase in operating voltage and nickel content, the cycle life of the material is also facing severe challenges.

[0005] As the voltage increases, more transition metals on the surface of the material will be oxidized and in a high valence state (e.g. nickel will mainly be Ni 4+ The high-valent ions at this time have strong oxidizing properties and can easily undergo redox reactions with organic electrolytes, leading to a series of problems such as electrolyte decomposition, transition metal dissolution, and gas production. How to suppress the side reactions at the interface under high voltage is currently a difficult problem.

[0006] In addition, more lithium ions are released from the bulk phase under high voltage, and the layered structure of the transition metal oxide is prone to sliding in the de-lithiation state, and the layered structure gradually disappears and turns to the spinel or rock salt phase structure. And as the charge and discharge cycle proceeds, the irreversible accumulation of sliding dislocations will also lead to cracks. With the anisotropic micro-stress caused by the deintercalation of lithium ions, the cracks will further expand, and the exposed fresh interface will aggravate the side reactions on the surface. Therefore, the stability of the layered structure of the material under high voltage also faces severe challenges.

[0007] Among the methods for modifying ternary materials, cobalt coating is one of the common modification methods for improving the capacity and cycle life of ternary single crystal materials. Constructing a cobalt coating layer on the surface of ternary materials can significantly improve the capacity and rate performance. However, the valence state of cobalt in the current cobalt coating layer is mostly Co 3+Cobalt coating does not improve the performance of the material at higher voltages. The cobalt coating also participates in charge storage at high voltages. As the voltage increases, especially when the voltage is above 4.45V, the Co 3+ Loses electrons and is oxidized to Co 4+ , due to Co 4+ It is very easy to reduce, and the orbitals of O2p and Co3d overlap. The lattice oxygen on the surface of the de-lithiated material easily reacts with the electrolyte to lose electrons, and the O 2 escape in the form of oxygen vacancies. 4+ Reduction easily causes phase change, resulting in the production of spinel phase Co3O4 and the dissolution of cobalt into the electrolyte. The coating on the surface of the material fails, the impedance of the material deteriorates, and the capacity decays rapidly during the cycle. This is also one of the common failure modes of the cobalt coating modification method under high voltage.

[0008] It should be noted that the information disclosed in the above background technology section is only used to enhance the understanding of the background of the present invention, and therefore may include information that does not constitute the prior art known to ordinary technicians in the field. Summary of the invention

[0009] In order to solve the above technical problems, the present invention provides a positive electrode material, a lithium ion battery and a preparation method.

[0010] According to a first aspect of the present invention, a positive electrode material is provided, the positive electrode material comprising a core and a coating layer, the core being a ternary material matrix, the coating layer being a fluorine-doped lithium cobalt oxygen material, the lithium cobalt oxygen material comprising Co 2+ and Co 3+ , and in the coating layer, fluorine element and Co 2+ They are distributed decreasingly from the surface to the center.

[0011] In an exemplary embodiment of the present invention, the coating layer is composed of the general formula Li 1+x Co 2+ y Co 3+ z N u O v F w It represents that, wherein x>0, 0.0<y≤1, 0.0<z≤1, 0.0≤u≤0.3, 0.0<v≤2, 0.0<w≤1; N is selected from one or more of Zr, W, Sr, Al, Ti, Mg, Nb, Cr, Cu, Zn, Y, Ca, B, P and Si.

[0012] In an exemplary embodiment of the present invention, the fluorine ion concentration on the surface of the positive electrode material is greater than or equal to 1%; 2+ The concentration is more than 70% of the total cobalt ion content on the surface of the positive electrode material.

[0013] In an exemplary embodiment of the present invention, the composition of the core is composed of the general formula Li e Ni a Co b Mn c M d O2 represents, wherein 0.7≤e≤1.05, 0.6≤a≤1.0, 0≤b≤0.33, 0≤c≤0.33, 0≤d≤0.05; M is selected from one or more of Zr, W, Sr, Al, Ti, Mg, Nb, Cr, Cu, Zn, Y, Ca, B, P, Si, S and F.

[0014] In an exemplary embodiment of the present invention, the core is a single crystal material with a particle size of 0.5 μm to 10 μm; and / or the coating layer has a thickness of 5 nm to 200 nm.

[0015] According to a second aspect of the present invention, there is provided a method for preparing the positive electrode material as described in any one of the above items, comprising:

[0016] S1, mixing a ternary precursor and a lithium source, and sintering them once in an oxygen or air atmosphere to obtain a ternary material matrix; or, mixing a ternary precursor, a lithium source and a dopant, and sintering them once in an oxygen-containing atmosphere to obtain a ternary material matrix; wherein the dopant is selected from one or more oxides or compounds of Zr, W, Sr, Al, Ti, Mg, Nb, Cr, Cu, Zn, Y, Ca, B, P, Si, S and F;

[0017] S2, secondary sintering the ternary material matrix with a lithium source, a cobalt source and a fluorine source in an oxygen-containing atmosphere to obtain the positive electrode material; or, secondary sintering the ternary material matrix with a lithium source, a cobalt source, a fluorine source and a coated dopant in an oxygen-containing atmosphere to obtain the positive electrode material.

[0018] In an exemplary embodiment of the present invention, in step S1, the primary sintering temperature is 800°C to 1000°C, the sintering atmosphere is 90% to 100% oxygen atmosphere; the heating rate is 2°C / min to 20°C / min, and the holding time is 8h to 15h.

[0019] In an exemplary embodiment of the present invention, in step S1 and step S2, the secondary sintering temperature is 300°C to 800°C, the sintering atmosphere is 60% to 1000% oxygen atmosphere; the heating rate is 2°C / min to 20°C / min, and the holding time is 8h to 15h.

[0020] In an exemplary embodiment of the present invention, in step S2, the cobalt source is selected from one or more of Co(OH)2, CoOOH, and Co3O4; the fluorine source is selected from one or more of LiF, MgF2, AlF3, CeF3, ZrF4, and CaF2; and in steps S1 and S2, the lithium source is selected from one or more of LiF, LiOH, Li2CO3, LiNO3, and Li3PO4.

[0021] According to a third aspect of the present invention, there is provided a lithium-ion battery, comprising the positive electrode material as described in any one of the above items, or the positive electrode material prepared by the preparation method as described in any one of the above items.

[0022] The positive electrode material, lithium ion battery and preparation method of the present invention have the following beneficial effects:

[0023] Compared with the common cobalt coating, the positive electrode material provided in the embodiment of the present invention adds excess lithium and fluorine elements during the cobalt coating, regulates the valence state of the Co element through charge compensation, and constructs a Co coating layer on the surface of the material. 2+ At most, it gradually decreases inward until the entire body is Co 3+ The fluoride ions in the coating layer also have a concentration gradient, which can effectively improve the capacity attenuation problem under high voltage, and show excellent cycle ability, high capacity and low impedance under high voltage. 2+ First, it is oxidized to Co 3+ , and then from Co 3+ Oxidized to Co 4+ , under the same high voltage, the Co on the surface of the delithiation material 4+ The concentration is reduced, which reduces the problem of oxygen precipitation due to charge compensation of lattice oxygen and the production of spinel phase Co3O4, and reduces the attenuation of the material's electron and ion transmission capacity during the cycle. Therefore, the impedance decreases with the increase of the cycle, and the cycle capacity under high voltage is improved.

[0024] In addition, the coating layer of the positive electrode material has Co 3+ / Co 2+ The introduction of this redox couple can 3+ and Co 2+A pathway for electron jumping is formed between the two materials, and a built-in electric field effect can be generated, thereby improving the diffusion dynamics of electrons and ions, reducing the charge transfer impedance, and improving the capacity rate performance of the material. This also makes up for the capacity and impedance deterioration caused by the introduction of fluorine.

[0025] Furthermore, in the coating layer of the positive electrode material, the fluorine ion concentration is greater than 1.0%, and has a concentration gradient, which decreases gradually inward. Without affecting the bulk capacity, the material's cycle performance is further improved by regulating the surface fluorine element. Specifically, the introduction of fluorine element not only regulates the Co in the cobalt coating layer, but also increases the cycle performance of the material. 2+ In addition to the concentration, the fluorine element itself also has the effect of improving the cycle. First, after the fluorine element replaces O in the lithium-rich fluorine-doped cobalt coating, its F-Co bond is longer than the surrounding O-Co bond. At the same time, the F element has a strong attraction to electrons, which can make the transition metal layer in the delithiation state more difficult to slip, and can improve the layered structure of the material, inhibiting the collapse of the layered structure in the high-voltage deep delithiation state. At the same time, O-position doping F can make the O2p state density below the Fermi level move toward the low energy level, reducing the overlap of Co3d-O2p orbits, thereby inhibiting the electron loss of oxygen on the surface of the material cobalt coating, reducing the activity of surface side reactions, and thus reducing the side reactions between the material surface and the electrolyte salt (including hexafluorophosphate, lithiated fluorophosphate, etc.). At the same time, the coating layer after surface fluorine modification has better corrosion resistance to electrolyte salts, which also greatly reduces the reaction between residual lithium on the surface of the material and the electrolyte solvent, including the reaction between surface lithium carbonate and lithium hexafluorophosphate, and surface lithium hydroxide and solvent, further reducing the risk of gas production.

[0026] Furthermore, in the positive electrode material of the embodiment of the present invention, the coating layer is a lithium cobalt oxide material. The increase in the lithium content of the surface layer can promote the synthesis of high stoichiometric components on the surface layer while improving the crystallinity of the coating layer, thereby inhibiting the "cation mixing" on the surface of the material (due to Ni 2+ With Li + The ionic radius of the ternary material is similar, and the positions of some ions are easily interchanged), which improves the stability of the crystal layered structure in the delithiation state after the lithium ions are released, and improves the cycle capacity of the material. In addition, during the first charge and discharge process of the ternary material, a certain proportion of lithium ions will not be re-embedded into the compound after being released from the crystal. This is related to the partial irreversibility or irreversible chemical reaction of the oxide crystal structure in the charged state and the solid electrolyte film produced on the surface of the positive electrode material. The amount of lithium ions that are not re-embedded into the compound directly affects the initial efficiency and capacity performance of the material. In the coating layer of the embodiment of the present invention, the increase in the surface lithium content can also make up for this part of the lithium ions that do not return to the positive electrode, thereby improving the capacity performance of the material. The increase in lithium content can also widen the size of the lithium layer in the crystal structure, thereby increasing the transmission rate of lithium ions and improving the rate and capacity performance of the material.

[0027] It is to be understood that the foregoing general description and the following detailed description are exemplary and explanatory only and are not restrictive of the present disclosure. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] In order to more clearly illustrate the technical solutions of the embodiments of the present disclosure, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present disclosure and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without paying creative work.

[0029] Figure 1 This is an electron microscope image of the positive electrode material obtained in Example 1 of the present invention.

[0030] Figure 2 This is an electron microscope image of the positive electrode material obtained in Comparative Example 1 of the present invention.

[0031] Figure 3 The surface Co valence distribution of the positive electrode material obtained in Example 1 of the present invention in the XPS test.

[0032] Figure 4 The surface Co valence distribution of the positive electrode material obtained in Comparative Example 1 of the present invention in the XPS test.

[0033] Figure 5 The figure is a comparison chart of the cycle performance of the positive electrode materials prepared in the embodiment of the present invention and the comparative example. DETAILED DESCRIPTION

[0034] In order to make the purpose, technical scheme and advantages of the embodiments of the present disclosure clearer, the technical scheme in the embodiments of the present disclosure will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.

[0035] The positive electrode material, lithium ion battery and preparation method of the embodiments of the present invention are described in detail below.

[0036] The embodiment of the present invention provides a positive electrode material, which includes a core and a coating layer. The core is a ternary material matrix, and specifically, the ternary material matrix is ​​a nickel-cobalt-manganese ternary material. Further, in a preferred embodiment of the present invention, the composition of the core can be a general formula Li e Ni a Co b Mn c M dO2 represents, wherein, 0.7≤e≤1.05, 0.6≤a≤1.0, 0≤b≤0.33, 0≤c≤0.33, 0≤d≤0.05; M is selected from one or more of Zr, W, Sr, Al, Ti, Mg, Nb, Cr, Cu, Zn, Y, Ca, B, P, Si, S and F. M is a doping element of the ternary material matrix, and the electrochemical properties of the material can be further improved by selecting different elements to dope the ternary material matrix.

[0037] Specifically, in this embodiment, the coating layer is a fluorine-doped lithium cobalt oxide material, and the lithium cobalt oxide material contains Co 2+ and Co 3+ Furthermore, the coating layer is composed of the general formula Li 1+x Co 2+ y Co 3+ z N u O v F w Represents, where x>0, 0.0<y≤1, 0.0<z≤1, 0.0≤u≤0.3, 0.0<v≤2, 0.0<w≤1.

[0038] Furthermore, N is a doping element of the coating layer, and N is selected from one or more of Zr, W, Sr, Al, Ti, Mg, Nb, Cr, Cu, Zn, Y, Ca, B, P and Si.

[0039] Furthermore, in this embodiment, the fluorine ion concentration on the surface of the positive electrode material is greater than or equal to 0.8%. More preferably, the fluorine ion concentration on the surface of the positive electrode material is greater than or equal to 1%; and in the coating layer, the fluorine element is distributed in a decreasing manner from the surface to the center. Experiments show that when the fluorine ion concentration on the surface of the positive electrode material is greater than 1%, it can not only ensure the 2+ regulation effect, and exhibits more excellent cycle performance.

[0040] It should be noted that the concentration of fluoride ions on the surface of the positive electrode material is the proportion of fluoride ions in all elements on the surface of the positive electrode material. The concentration of fluoride ions can be obtained by XPS testing. For specific testing methods, please refer to the description in Experimental Example 1 below.

[0041] Furthermore, in this embodiment, the cobalt content of the positive electrode material is 0.5% to 3.5% of the total weight of the ternary material matrix. Specifically, the mass of cobalt in the coating layer and the mass of the ternary material matrix satisfy: 0.5% ≤ m (cobalt) / m (ternary material matrix) * 100% ≤ 3.5wt%. By adjusting the cobalt content, it is ensured that the gradient distribution of Co is achieved under the participation of Li and F. 2+ .

[0042] More preferably, the Co on the surface of the positive electrode material 2+ The concentration is more than 70% of the total cobalt ion content on the surface of the positive electrode material. 2+ and Co 3+ Coexistence, surface Co 2+ The concentration is the highest, reaching more than 70%, and gradually decreases inward. 2+ Concentration can further improve the attenuation of the material's electron and ion transmission capabilities during the cycle and enhance the cycle performance under high voltage.

[0043] It should be noted that the Co 2+ The concentration can be obtained through XPS testing. For the specific testing method, please refer to the description in Experimental Example 1 below.

[0044] Further, in this embodiment, the core is a single crystal material, and its particle size is 0.5 μm to 10 μm. Further, in this embodiment, the thickness of the coating layer is 5 nm to 200 nm.

[0045] The present invention also provides a method for preparing the positive electrode material, comprising:

[0046] S1, mixing the ternary precursor and the lithium source, and sintering once in an oxygen or air atmosphere to obtain a ternary material matrix. The ternary precursor TM(OH)2 can be, for example, Ni 0.63 Co 0.09 Mn 0.27 (OH)2, etc. The ternary precursor can be synthesized by solid phase method, hydrothermal method, etc., and the present disclosure does not impose any specific restrictions. The ternary material matrix is ​​not doped, that is, the structural formula Li e Ni a Co b Mn c M d In O2, d=0.

[0047] In another embodiment of the present invention, step S1 may also include mixing a ternary precursor, a lithium source and a matrix dopant, and sintering once in an oxygen-containing atmosphere to obtain a ternary material matrix. The matrix dopant is selected from one or more oxides or compounds of Zr, W, Sr, Al, Ti, Mg, Nb, Cr, Cu, Zn, Y, Ca, B, P, Si, S and F. For example, the matrix dopant is ZrO2, TiO2, Al2O3, etc., but is not limited thereto.

[0048] Further, in step S1, the lithium source is selected from one or more of LiF, LiOH, Li2CO3, LiNO3, Li3PO4, but is not limited thereto.

[0049] Further, in step S1, the temperature of the primary sintering is 800°C to 1000°C, for example, 800°C, 820°C, 840°C, 860°C, 880°C, 900°C, 950°C, 1000°C, etc., but not limited thereto. The sintering atmosphere is 90% to 100% oxygen atmosphere, for example, 93%, 95%, 98% oxygen atmosphere, etc., but not limited thereto. The heating rate is 2°C / min to 20°C / min. For example, the heating rate may be 2°C / min, 5°C / min, 7°C / min, 10°C / min, 13°C / min, 15°C / min, 18°C / min, 20°C / min, etc., but not limited thereto. The holding time of the primary sintering is 8h to 15h, for example, 8h, 9h, 10h, 11h, 12h, 13h, 14h, 15h, etc., but not limited thereto.

[0050] After obtaining the ternary material matrix, step S2 is performed to perform secondary sintering of the ternary material matrix with a lithium source, a cobalt source and a fluorine source in an oxygen-containing atmosphere to obtain the positive electrode material. 1+x Co 2+ y Co 3+ z N u O v F w In, u=0.

[0051] It is understood that in another embodiment of the present invention, the coating layer can be doped, and step S2 includes: secondary sintering the ternary material matrix with a lithium source, a cobalt source, a fluorine source and a coating dopant in an oxygen-containing atmosphere to obtain the positive electrode material. The coating dopant is selected from one or more oxides or salts of Zr, W, Sr, Al, Ti, Mg, Nb, Cr, Cu, Zn, Y, Ca, B, P and Si. For example, the coating dopant can be Nb2O3, MgO, etc., but is not limited thereto.

[0052] Furthermore, in step S2, the secondary sintering temperature is 300°C to 800°C, and more preferably, the secondary sintering temperature is 500°C to 700°C. For example, 500°C, 550°C, 600°C, 650°C, etc. If the secondary sintering temperature is too high, it is easy to cause the surface Co 2+ The concentration decreases.

[0053] Further, in step S2, the sintering atmosphere is 60-100% oxygen atmosphere; for example, 73%, 75%, 78%, oxygen atmosphere, etc., but not limited to this. The heating rate is 2°C / min to 20°C / min, for example, the heating rate can be 2°C / min, 5°C / min, 7°C / min, 10°C / min, 13°C / min, 15°C / min, 18°C / min, 20°C / min, etc., but not limited to this. The insulation time is 8h to 15h. For example, 8h, 9h, 10h, 11h, 12h, 13h, 14h, 15h, etc., but not limited to this.

[0054] Furthermore, in step S2, the cobalt source is selected from one or more of Co(OH)2, CoOOH, and Co3O4.

[0055] Furthermore, in step S2, the fluorine source is selected from one or more of LiF, MgF2, AlF3, CeF3, ZrF4, and CaF2. Preferably, the fluorine source is LiF.

[0056] Furthermore, in step S2, the lithium source is selected from one or more of LiF, LiOH, Li2CO3, LiNO3, Li3PO4, but is not limited thereto.

[0057] In the above preparation method, compared with first preparing the material of the coating layer and then coating by blending, in this embodiment, the coating layer formed on the surface of the ternary material matrix by the secondary sintering method, Co 2+ During the sintering process, the F ions will be distributed in the coating layer in the form of a concentration gradient, which inhibits the "cation mixing" on the surface of the material. After the lithium ions are released, the stability of the crystal layered structure in the delithiation state is better, there are fewer surface side reactions, and it has a better cycle capacity.

[0058] The present invention also provides a lithium-ion battery, comprising a positive electrode, a negative electrode and an electrolyte, wherein the positive electrode comprises the positive electrode material mentioned above. It is understood that the lithium-ion battery can be manufactured according to a known method in the prior art.

[0059] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.

[0060] Example 1

[0061] This embodiment provides a positive electrode material, which is obtained by following the steps below:

[0062] Step (1): nickel sulfate, cobalt sulfate and manganese sulfate are prepared into a soluble salt solution with a total nickel, cobalt and manganese metal ion concentration of 110 g / L according to the stoichiometric ratio of nickel, cobalt and manganese elements of 0.63:0.09:0.27; 30 L of 4 g / L ammonia solution is pumped into a high temperature and high pressure reactor as the reactor bottom liquid, oxygen with a purity of 60% is introduced into the reactor, the stirring device of the reactor is turned on, the temperature of the reactor is controlled at 50°C, and the reaction product is dried and calcined to obtain a ternary precursor Ni 0.63 Co 0.09 Mn 0.27 (OH)2.

[0063] Step (2): Add the matrix dopant ZrO2, Al2O3, lithium hydroxide, and the ternary precursor NCM obtained in step (1) to a high-speed mixer at a molar ratio of lithium to NCM metal of 1:1, with a mixing speed of 500 r / min and a mixing time of 20 min to obtain a corresponding mixture. The mixture is sintered at 950° C. for 20 h in a 95% oxygen atmosphere, and then crushed at high strength to obtain a uniformly dispersed ternary material matrix.

[0064] Step (3): Add the ternary material matrix prepared in step (2) and lithium hydroxide, lithium fluoride and cobalt tetroxide in a mass ratio of ternary material matrix: Li: F: Co = 1: 0.005: 0.02: 0.02 into a high-speed mixer for mixing, the mixing speed is 600 r / min, the mixing time is 20 min, and the corresponding mixture is obtained; the obtained mixture is sintered at 650° C. for 10 h in a 75% oxygen atmosphere to obtain a ternary positive electrode material with a coating layer.

[0065] Example 2

[0066] This embodiment provides a positive electrode material, which is different from the embodiment 1 in that:

[0067] In step (3), the mass ratio of the ternary material matrix is: Li:F:Co=1:0.005:0.015:0.02.

[0068] The remaining steps are the same as those in Example 1.

[0069] Example 3

[0070] This embodiment provides a positive electrode material, which is different from the embodiment 1 in that:

[0071] In step (3), the mass ratio of the ternary material matrix is: Li:F:Co=1:0.002:0.015:0.02.

[0072] The remaining steps are the same as those in Example 1.

[0073] Example 4

[0074] This embodiment provides a positive electrode material, which is different from the embodiment 1 in that:

[0075] In step (3), the mass ratio of the ternary material matrix is: Li:F:Co=1:0.005:0.01:0.02.

[0076] The remaining steps are the same as those in Example 1.

[0077] Example 5

[0078] This embodiment provides a positive electrode material, which is different from the embodiment 1 in that:

[0079] In step (3), the ternary material matrix is ​​Li:F:Co=1:0.002:0.01:0.02 in terms of mass ratio.

[0080] The remaining steps are the same as those in Example 1.

[0081] Example 6

[0082] This embodiment provides a positive electrode material, which is different from the embodiment 1 in that:

[0083] In step (3), the ternary material matrix and lithium hydroxide, lithium fluoride, cobalt tetroxide, and dopant niobium oxide are added into a high-speed mixer in a mass ratio of ternary material matrix: Li: F: Co: Nb = 1: 0.005: 0.01: 0.02: 0.001, and the mixing speed is 600 r / min and the mixing time is 20 min to obtain the corresponding mixture; the obtained mixture is sintered at 650° C. for 10 h in a 75% oxygen atmosphere to obtain a ternary positive electrode material with a coating layer.

[0084] The remaining steps are the same as those in Example 1.

[0085] Example 7

[0086] This embodiment provides a positive electrode material, which is different from the embodiment 1 in that the sintering temperature in step (3) is 750° C. The remaining steps are the same as those in the embodiment 1.

[0087] Comparative Example 1

[0088] This comparative example provides a positive electrode material, which is different from Example 1 in that:

[0089] Step (3): Add the ternary material matrix prepared in step (2) and cobalt oxide in a mass ratio of ternary material matrix: Co = 1:0.02 into a high-speed mixer for mixing, the mixing speed is 600r / min, the mixing time is 20min, and the corresponding mixture is obtained; the obtained mixture is sintered at 650°C for 10h in a 75% oxygen atmosphere to obtain a ternary positive electrode material with a coating layer.

[0090] The remaining steps are the same as those in Example 1.

[0091] Comparative Example 2

[0092] This comparative example provides a positive electrode material, which is different from Example 1 in that:

[0093] Step (3): Add the ternary material matrix prepared in step (2) and lithium hydroxide and cobalt oxide in a mass ratio of ternary material matrix: Li: Co = 1: 0.005: 0.02 into a high-speed mixer for mixing, the mixing speed is 600 r / min, the mixing time is 20 min, and the corresponding mixture is obtained; the obtained mixture is sintered at 650° C. for 10 h in a 75% oxygen atmosphere to obtain a ternary positive electrode material with a coating layer.

[0094] The remaining steps are the same as those in Example 1.

[0095] Comparative Example 3

[0096] This comparative example provides a positive electrode material, which is different from Example 1 in that:

[0097] Step (3): Add the ternary material matrix prepared in step (2) and lithium fluoride and cobalt oxide in a mass ratio of ternary material matrix: F: Co = 1: 0.01: 0.02 into a high-speed mixer for mixing, the mixing speed is 600r / min, the mixing time is 20min, and the corresponding mixture is obtained; the obtained mixture is sintered at 650°C for 10h in a 75% oxygen atmosphere to obtain a ternary positive electrode material with a coating layer.

[0098] Test Example 1Co 2+ 、Co 3+ , F content determination

[0099] The Co of the positive electrode materials prepared in Examples 1 to 7 and Comparative Examples 1 to 3 was measured by X-ray photoelectron spectroscopy (XPS). 2+ 、Co 3+ The concentration of fluoride ions was also determined.

[0100] The specific test process is as follows: Al-Kα is used as the ray source (energy hν=1486.6eV) to etch the surface of the material, the etching depth is the surface and 10nm depth, and the C1s peak binding energy 284.80eV is used as the charge correction standard; the fine spectra of Co2p and F1s in the obtained energy spectrum are further analyzed, and deconvolution is performed according to the unified characteristic peak position to obtain the relative proportion of different chemical states of Co and the concentration of fluoride ions. The results are shown in Table 1:

[0101] Table 1

[0102]

[0103] It can be seen from Table 1 that in the embodiment of the present invention, Co 2+ and F ions gradually decrease from the surface to the center. 2+ The content of Co is extremely low. 2+ In comparative example 3, no lithium source was added during coating, and the surface Co 2+ The increase in content is not obvious.

[0104] Test Example 2 Electrochemical Performance Test

[0105] The positive electrode materials, superconducting carbon black SP and polyvinylidene fluoride PVDF prepared in Examples 1 to 7 and Comparative Examples 1 to 3 were mixed in a mass ratio of 94:3:3, and the mixture was adjusted into a slurry with N-methyl-pyrrolidone (NMP); the slurry was evenly coated on the aluminum foil current collector to obtain a positive electrode film. A metal lithium sheet was used as the negative electrode, a polypropylene microporous membrane was used as the diaphragm, and 1mol / LiPF6 (the solvent was a mixture of ethylene carbonate and dimethyl carbonate in a volume ratio of 1:1) was used as the electrolyte to assemble a button cell in an Ar gas-protected glove box. The following tests were performed respectively:

[0106] a) The button cell prepared above was subjected to a capacity test under the conditions of 25° C., 2.8V-4.5V, 0.1CV / 0.1CD;

[0107] b) After the capacity test of the button cell, the cycle capacity test was performed under the following test conditions: 45°C, 2.5-4.5V, 0.5CV / 1.0CD, and 50 cycles.

[0108] The test results are shown in Table 2 and Figure 1 As shown:

[0109] Table 2

[0110]

[0111]

[0112] From Table 2 and Figure 1 It can be seen that in this embodiment, during the coating, Li and F are used to coat Co. 2+ Coordinated regulation makes the surface of the ternary cathode material have a higher Co 2+ and fluoride ion concentration, and has a concentration gradient, and has excellent capacity and cycle performance at high voltage. In addition, in Example 6, the coating layer is additionally doped and modified to further improve the cycle performance of the material.

[0113] The above description is not all embodiments. The detailed description of the embodiments of the present disclosure is not intended to limit the scope of the present disclosure for protection, but merely represents selected embodiments of the present disclosure. Based on the embodiments in the present disclosure, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present disclosure.

Claims

1. A positive electrode material, characterized in that: The positive electrode material comprises a core and a coating layer, wherein the core is a ternary material matrix, and the coating layer is a fluorine-doped lithium cobalt oxygen material, wherein the lithium cobalt oxygen material contains Co 2+ and Co 3+ , and in the coating layer, fluorine element and Co 2+ They are distributed decreasingly from the surface to the center.

2. The positive electrode material according to claim 1, characterized in that The coating layer is composed of the general formula Li 1+x Co 2+ y Co 3 + z N u O v F w It represents that, wherein x>0, 0.0<y≤1, 0.0<z≤1, 0.0≤u≤0.3, 0.0<v≤2, 0.0<w≤1; N is selected from one or more of Zr, W, Sr, Al, Ti, Mg, Nb, Cr, Cu, Zn, Y, Ca, B, P and Si.

3. The positive electrode material according to claim 2, characterized in that The fluoride ion concentration on the surface of the positive electrode material is greater than or equal to 1%; the Co 2+ The concentration is more than 70% of the total cobalt ion content on the surface of the positive electrode material.

4. The positive electrode material according to claim 1, characterized in that The composition of the core is composed of the general formula Li e Ni a Co b Mn c M d O2 represents, wherein 0.7≤e≤1.05, 0.6≤a≤1.0, 0≤b≤0.33, 0≤c≤0.33, 0≤d≤0.05; M is selected from one or more of Zr, W, Sr, Al, Ti, Mg, Nb, Cr, Cu, Zn, Y, Ca, B, P, Si, S and F.

5. The positive electrode material according to claim 1, characterized in that The inner core is a single crystal material, and its particle size is 0.5 μm to 10 μm; and / or the coating layer has a thickness of 5 nm to 200 nm.

6. A method for preparing a positive electrode material according to any one of claims 1 to 5, characterized in that: include: S1, mixing the ternary precursor and the lithium source, and sintering once in an oxygen or air atmosphere to obtain a ternary material matrix; Alternatively, a ternary precursor, a lithium source and a matrix dopant are mixed and sintered once in an oxygen-containing atmosphere to obtain a ternary material matrix; wherein the dopant is selected from one or more oxides or compounds of Zr, W, Sr, Al, Ti, Mg, Nb, Cr, Cu, Zn, Y, Ca, B, P, Si, S and F; S2, secondary sintering the ternary material matrix with a lithium source, a cobalt source and a fluorine source in an oxygen-containing atmosphere to obtain the positive electrode material; or, secondary sintering the ternary material matrix with a lithium source, a cobalt source, a fluorine source and a coated dopant in an oxygen-containing atmosphere to obtain the positive electrode material.

7. The method for preparing the positive electrode material according to claim 6, characterized in that: In step S1, the primary sintering temperature is 800°C to 1000°C, the sintering atmosphere is 90% to 100% oxygen atmosphere; the heating rate is 2°C / min to 20°C / min, and the insulation time is 8h to 15h.

8. The method for preparing the positive electrode material according to claim 6, characterized in that: In step S1 and step S2, the secondary sintering temperature is 300°C to 800°C, the sintering atmosphere is 60% to 100% oxygen atmosphere; the heating rate is 2°C / min to 20°C / min, and the insulation time is 8h to 15h.

9. The method for preparing the positive electrode material according to claim 6, characterized in that: In step S2, the cobalt source is selected from one or more of Co(OH)2, CoOOH, and Co3O4; the fluorine source is selected from one or more of LiF, MgF2, AlF3, CeF3, ZrF4, and CaF2; in steps S1 and S2, the lithium source is selected from one or more of LiF, LiOH, Li2CO3, LiNO3, and Li3PO4.

10. A lithium ion battery, characterized in that: The invention comprises the positive electrode material according to any one of claims 1 to 5, or the positive electrode material prepared by the preparation method according to any one of claims 6 to 9.

Citation Information

Cited By

  • Cathode material with coating layer, preparation method of cathode material and lithium ion battery

    CN119890275A

  • Positive electrode material and preparation method thereof, electrochemical device and electronic equipment

    CN121149219A

  • A positive electrode material, a preparation method thereof, an electrochemical device, and an electronic device

    CN121149219B

  • High-dispersity medium-high nickel single crystal ternary positive electrode material, preparation method thereof and lithium ion battery

    CN121394341A

  • A highly dispersed medium-high nickel single-crystal ternary cathode material, its preparation method, and a lithium-ion battery.

    CN121394341B